2015
DOI: 10.28945/2283
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Facebook Application in Undergraduate Learning: A Study of Jordanian Students

Abstract: The purpose of this paper was to explore the current and potential use of Facebook for learning purposes by Jordanian university students. The paper attempted to compare such use with other uses of Facebook. Further, the paper investigated Jordanian university students' attitudes towards using Facebook as a formal academic tool, through the use of course-specific Facebook groups.To that end, quantitative data were collected from a sample of 451 students from three Jordanian public universities. Findings indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Research has shown that many students believe that using Social Networking Systems (SNS) such as Facebook and Twitter in class would be convenient (Alarabiat & Al-Mohammad, 2015;Karl & Peluchette, 2011;Roblyer, McDaniel, Webb, Herman, & Witty, 2010), as these systems are an integral part of their daily lives (Alarabiat & Al-Mohammad, 2015;Johnston, 2013). In a study of schools, Ruggiero and Mong (2015) found teachers used mobiles in the classroom to share ideas using social networking systems, as well as for email, attendance systems, and research.…”
Section: Use Of Mobile Web-enabled Devices In the Classroommentioning
confidence: 99%
See 4 more Smart Citations
“…Research has shown that many students believe that using Social Networking Systems (SNS) such as Facebook and Twitter in class would be convenient (Alarabiat & Al-Mohammad, 2015;Karl & Peluchette, 2011;Roblyer, McDaniel, Webb, Herman, & Witty, 2010), as these systems are an integral part of their daily lives (Alarabiat & Al-Mohammad, 2015;Johnston, 2013). In a study of schools, Ruggiero and Mong (2015) found teachers used mobiles in the classroom to share ideas using social networking systems, as well as for email, attendance systems, and research.…”
Section: Use Of Mobile Web-enabled Devices In the Classroommentioning
confidence: 99%
“…In a study of schools, Ruggiero and Mong (2015) found teachers used mobiles in the classroom to share ideas using social networking systems, as well as for email, attendance systems, and research. Alarabiat and Al-Mohammad (2015) explored the use of Facebook for learning in three Jordanian universities. Similarly to most students globally, the majority of Jordanian students were members of Facebook and spent a considerable amount of time daily on Facebook.…”
Section: Use Of Mobile Web-enabled Devices In the Classroommentioning
confidence: 99%
See 3 more Smart Citations